2007
DOI: 10.1007/s11938-007-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics and quality of life of current and emerging biologic therapies for inflammatory bowel disease

Abstract: The development of biologic therapies for Crohn's disease and ulcerative colitis has profoundly affected the treatment of these diseases. The impact of these novel therapies has been tremendous in terms of their ability to cause clinical improvement in symptoms and endoscopic and histologic evidence of healing, as well as improvements in quality of life. However, the success of these new remedies comes with a significant price tag. In the current cost-containment environment of health care, it is essential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…12-14,31-34 We believe the unique value of this study is that it offers a quantitative “snapshot” of utilization trends, although single-center, under standard of care models for IBD in a large tertiary academic center. To our knowledge, no study has tried to describe and compare longitudinal utilization trends for both infliximab and adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…12-14,31-34 We believe the unique value of this study is that it offers a quantitative “snapshot” of utilization trends, although single-center, under standard of care models for IBD in a large tertiary academic center. To our knowledge, no study has tried to describe and compare longitudinal utilization trends for both infliximab and adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…If these hopes materialize these new therapies may prevent the progressive work disability that many CD patients experience. 30 Having a validated tool to measure work disability could help to determine the long-term efficacy of the different treatments in improving this severe consequence of the disease. Indeed, Feagan et al 4 have recommended including disability as an endpoint in therapeutic trials.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the Crohn's disease course and prognosis, HRQOL is diminished and directly correlates with a higher likelihood of unemployment [28]. In a case-controlled study [29], adult patients with CD were reported to have more long-term unemployment than controls.…”
Section: Indirect Costs: Total Economic Loss Experienced By Patientsmentioning
confidence: 99%